Barbados Insulin Matters (BIM) study: Perceptions on insulin initiation by primary care doctors in the Caribbean island of Barbados. Issue 2 (April 2017) - Taylor, Charles Grafton; Taylor, Gordon; Atherley, Anique; Hambleton, Ian; Unwin, Nigel; Adams, Oswald Peter
Highlights: Public sector PCDs reported a lack of support from other healthcare professionals. Public sector PCDs had a higher diabetes patient load and were under more time pressure when initiating insulin. All PCDs thought the availability of diabetes specialist nurses would improve insulin initiation. The majority of PCDs thought the benefits of insulin outweighed the risks. Reasons for reluctance to initiate insulin included: patient non-adherence and reluctance and older age. Abstract: Aims: With regards to insulin initiation in Barbados we explored primary care doctor (PCD) perception, healthcare system factors and predictors of PCD reluctance to initiate insulin. Methods: PCDs completed a questionnaire based on the theory of planned behaviour (TPB) and a reluctance to initiate insulin scale. Using linear regression, we explored the association between TPB domains and the reluctance to initiate insulin scale. Results: Of 161 PCDs, 70% responded (75 private and 37 public sector). The majority felt initiating insulin was uncomplicated (68%) and there was benefit if used before complications developed (68%), but would not use it until absolutely necessary (58%). More private than public sector PCDs ( p  < 0.05) thought that the healthcare system allowed enough flexibility of time for education (68 vs 38%) and initiating insulin was easy (63 vs 35%), but less thought system changes would help initiating insulin (42 vs 70%). Reasons for reluctance to initiate insulin included patient nonadherence (83%) and reluctance (63%). Only the attitudes and belief domain of the TPB was associated with the reluctance to initiate insulin scale ( p  < 0.001). Conclusions: Interventions focusing on PCD attitudes and beliefs and restructuring services inclusive of the use of diabetes specialist nurses are required.